Peculiarities of translation of japanese somatic idioms into Russian (on the material of somatic idioms with the components «head», «eye», «hand») (Journal of Oriental Studies, 2016)
This paper is dedicated to examine methods of translation of Japanese somatic idioms into Russian. In this paper we examined factors that influence on idiom equivalents, discovered idiom equivalents in two languages, and examined methods of translation of somatic idioms.
Keywords: idiom; somatic idiom units; equivalence; methods of translation; Japanese language; Russian language.